Hubungan Motivasi Belajar dengan Prokrastinasi Akademik Siswa di Sekolah Menengah Pertama - Friska Zuherma Putri; Dina Sukma (ANWARUL, 2024)
This research is motivated by the phenomenon of many students engaging in academic procrastination at school. Forms of academic procrastination include students making assignments in class while the teacher is explaining the subject matter, copying friends' assignments, not completing assignments, and submitting assignments beyond the time limit. Students also stated that their reasons for carrying out academic procrastination were that the large number of assignment demands given by teachers in each subject with a deadline of only a few days meant that students were unable to do their assignments well. This research aims to (1) describe the picture of students' learning motivation. SMPN 26 Padang, (2) describe the picture of academic procrastination of SMPN 26 Padang students, and (3) examine the relationship between learning motivation and academic procrastination of SMPN 26 Padang students. This research uses quantitative methods with a correlational research type. The sample in this study was 167 students selected using the Proportional Random Sampling technique. The data was processed using descriptive analysis and Pearson product moment correlation analysis using the SPSS version 20 for Windows program. The results of this study show that (1) students' learning motivation is in the medium category with a percentage of (35.9%), (2) students' academic procrastination is in the high category with a percentage of (56.9%), (3) there is a significant relationship and has a negative direction between learning motivation and academic procrastination with a calculated r correlation value of -0.312 with a significance level of 0.000 at the weak relationship level.